Crude Oil Biodegradation Potential using Acinetobacter baumannii CYA20 and Bacillus subtilis CYA27 from the Bekasi Coast, Indonesia - Christy Nur Cahyani; Andes Ismayana; Mohamad Yani (Bogor Agricultural University, Indonesia, 2022)
The pollution of coastal areas caused by oil spills is an environmental issue that needs further attention. Crude oil contains persistent organic pollutants (POPs) that are difficult to degrade. This study aimed to isolate bacterial strains capable of degrading crude oil from the Bekasi coast through bacterial isolate characterization and crude oil biodegradation tests using a crude oil-enriched microcosm model. Two strains with higher TPH degradation values were selected among the isolated bacteria, namely CYA20 and CYA27, which specifically showed values of 46% and 66%, respectively. These strains were tolerant to NaCl concentrations of up to 4% and 12%, respectively, and they were also tolerant to pH values ranging from 5 to 9 and temperatures between 10°C and 50°C. Both strains were shown to utilize POPs, such as phenanthrene and fluorene, produce biosurfactants, and exhibited an emulsification activity in paraffin ranging from 0.373 to 0.533. Phylogenetic analyses identified these bacterial strains as Acinetobacter baumannii CYA20 and Bacillus subtilis CYA27, respectively. The results of this study indicate that these isolates could be developed as biodegradation agents for the bioremediation of crude oil-contaminated environments.